Perioperative chemotherapy versus surgery alone for resectable colorectal liver metastases: an international multicentre propensity score matched analysis on long-term outcomes according to established prognostic risk scores. Issue 12 (December 2021) - Di Martino, Marcello; Primavesi, Florian; Syn, Nicholas; Dorcaratto, Dimitri; de la Hoz Rodríguez, Ángela; Dupré, Aurélien; Piardi, Tullio; Rhaiem, Rami; Blanco Fernández, Gerardo; Prada Villaverde, Arancha; Rodríguez Sanjuán, Juan C.; Fernández Santiago, Roberto; et al.
Abstract: Background: There is still uncertainty regarding the role of perioperative chemotherapy (CTx) in patients with resectable colorectal liver metastases (CRLM), especially in those with a low-risk of recurrence. Methods: Multicentre retrospective analysis of patients with CRLM undergoing liver resection between 2010–2015. Patients were divided into two groups according to whether they received perioperative CTx or not and were compared using propensity score matching (PSM) analysis. Then, they were stratified according to prognostic risk scores, including: Clinical Risk Score (CRS), Tumour Burden Score (TBS) and Genetic And Morphological Evaluation (GAME) score. Results: The study included 967 patients with a median follow-up of 68 months. After PSM analysis, patients with perioperative CTx presented prolonged overall survival (OS) in comparison with the surgery alone group (82.8 vs 52.5 months, p = 0.017). On multivariable analysis perioperative CTx was an independent predictor of increased OS (HR 0.705, 95%CI 0.705–0.516, p = 0.029). The benefits of perioperative CTx on survival were confirmed in patients with CRS and TBS scores ≤2 (p = 0.022 and p = 0.020, respectively) and in patients with a GAME score ≤1 (p = 0.006). Conclusion: Perioperative CTx demonstrated an increase in OS in patients with CRLM. Patients with a low-risk of recurrence seem to benefit from systemic treatment.